Versatile Ion-polarized Techniques On-line (VITO) experiment at ISOLDE-CERN - Stachura, M.
The VITO (Versatile Ion-polarized Techniques Online) project is a new experimental setup at the ISOLDE facility at CERN. VITO is a dedicated beam line for producing laser-induced spin-polarized beams of both, atoms and ions, and it has been commissioned in response to the continuously growing demand for the use of spin-polarized beams. The new VITO beam line is a modification of the formerly existing ultra-high vacuum beam line, connecting ASPIC (Apparatus for Surface Physics and Interfaces at CERN), and it has been under construction since the beginning of 2014. Once fully commissioned, VITO will open up numerous possibilities for carrying out multidisciplinary experiments in the areas of nuclear and solid state physics, fundamental interaction physics and biophysics. In its final stage the VITO beam line will provide three fully independent experimental stations: UHV chamber for material science applications, a P-asymmetry station where highly-polarized ions will be available, and a central open-end station suitable for travelling experiments. The VITO beam line will operate in two different modes providing either beams of spin-polarized atoms or ions, or non-polarized ion beams to all three end stations operating from 10(-10) mbar to 50 mbar. Recent experimental campaigns with stable and radioactive beams have allowed for testing VITO's constituent parts and have demonstrated 96% of ion beam transmission to the collection chamber installed on the central station. The first experimental results obtained with on-line Perturbed Angular Correlation (PAC) spectroscopy using Cu-68m ion-beams will be briefly discussed. (C) 2016 Elsevier B.V. All rights reserved.